2020
DOI: 10.1136/bmjopen-2019-031629
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare-related cost of oropharyngeal dysphagia and its complications pneumonia and malnutrition after stroke: a systematic review

Abstract: ObjectivesTo assess the healthcare costs associated with poststroke oropharyngeal dysphagia (OD) and its complications (malnutrition, dehydration, pneumonia and death).DesignSystematic review following Preferred Reporting Items for Systematic Reviews and Meta-Analyses recommendations.Data sourcesMEDLINE, Embase and the National Health Service Economic Evaluation Database were searched up to 31 December 2019.ParticipantsPatients with poststroke.Primary outcome measuresThe costs associated to poststroke OD and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 28 publications
1
34
0
1
Order By: Relevance
“…4 Some health economic data on the cost and on sanitary resource consumption of post-stroke OD and its main complications have also been reported. 5,19 This shows an independent increase in costs associated with OD after stroke during hospitalization that can increase exponentially with the development of its main complications (malnutrition and respiratory infections) during long-term followup. In a recent study, we found the 1-year cost of a post-stroke patient with OD, malnutrition and at least one episode of respiratory infection is 19,817.58 ± 13,724.83 vs. 7,242.8 ± 7,402.6 euros, the latter of a post-stroke patient without OD, clearly showing the economic burden of post-stroke OD from both the Hospital and the Health Care System Perspectives.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…4 Some health economic data on the cost and on sanitary resource consumption of post-stroke OD and its main complications have also been reported. 5,19 This shows an independent increase in costs associated with OD after stroke during hospitalization that can increase exponentially with the development of its main complications (malnutrition and respiratory infections) during long-term followup. In a recent study, we found the 1-year cost of a post-stroke patient with OD, malnutrition and at least one episode of respiratory infection is 19,817.58 ± 13,724.83 vs. 7,242.8 ± 7,402.6 euros, the latter of a post-stroke patient without OD, clearly showing the economic burden of post-stroke OD from both the Hospital and the Health Care System Perspectives.…”
Section: Discussionmentioning
confidence: 98%
“…27,600 USD) based on studies performed in France, Switzerland, Argentina, Brazil, Taiwan and the United States. 5 Appropriate management and treatment of post-stroke OD is required to avoid clinical complications, improve patients' quality of life and to save healthcare resources. 3 Current treatment for post-stroke OD is not standardized and includes a series of strategies that can go from compensation measures, including uid thickening and texture-modi ed foods (classical treatment) 6 , to more innovative neurorehabilitation approaches including peripheral stimulation treatments (electrical and pharmacologic studies) and noninvasive brain stimulation techniques (NIBS).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Post-extubation dysphagia is a common complication in mixed intensive care units (ICUs), causing aspiration pneumonia, malnutrition, and dehydration, and increasing the length of hospital stay and mortality (1)(2)(3)(4)(5). The prevalence of postextubation dysphagia ranges from 3 to 62%, which leads to increased healthcare-related costs (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…2 Chronic poststroke oropharyngeal dysphagia is associated to significantly higher economic costs. 4 Pathophysiology of CPSOD has been associated with (a) bi-hemispheric reduction of efferent pathway's excitability with loss of motor dominance 5,6 and (b) reduced pharyngeal sensitivity 7 with disrupted cortical conduction/integration of pharyngeal sensory inputs at stroke site. 8 These dysfunctions and the uncoupling between sensory/motor swallowing circuitry cause the slow oropharyngeal swallow response (OSR) in these patients.…”
Section: Introductionmentioning
confidence: 99%